Generalizable design parameters for soluble T cell receptor-based T cell engagers - Flora Huang; Arlene Sereno; Karen J Froning; Stephen J Demarest (Journal for ImmunoTherapy of Cancer)
While most biological and cellular immunotherapies recognize extracellular targets, T cell receptor (TCR) therapeutics are unique in their ability to recognize the much larger pool of intracellular antigens found on virus-infected or cancerous cells. Recombinant T cell receptor (rTCR)-based therapeutics are gaining momentum both preclinically and clinically highlighted by recent positive phase III human clinical trial results for a TCR/CD3 bifunctional protein in uveal melanoma. Unlike antibody-based T cell engagers whose molecular formats have been widely and extensively evaluated, little data exist describing the putative activities of varied bifunctional formats using rTCRs. Here we generate rTCR/anti-CD3 bifunctionals directed toward NY-ESO-1 or MAGE-A3 with a variety of molecular formats. We show that inducing strong redirected lysis activity against tumors displaying either NY-ESO-1 or MAGE-A3 is highly restricted to small, tandem binding formats with an rTCR/antiCD3 Fab demonstrating the highest potency, rTCR/anti-CD3 single chain variable domain fragment showing similar but consistently weaker potency, and IgG-like or IgG-Fc-containing molecules demonstrating poor activity. We believe this is a universal trait of rTCR bifunctionals, given the canonical TCR/human leukocyte antigen structural paradigm.